Home-Based Treatment for Chronic Constipation. Issue 2 (May 2018) - Al-Momani, Laith Adel; Arikapudi, Sowminya; Gaddam, Sathvika; Treece, Jennifer; Rashid, Saima; Baumrucker, Steven
Chronic constipation is a very common problem that negatively affects the quality of life of patients, especially the elderly population. It can also lead to significant health care expenditure. Careful assessment by obtaining a thorough history and physical examination with limited indicated diagnostic testing is important to identify potential underlying etiologies and to treat effectively.